ANTECEDENTS OF AI-DRIVEN ACCOUNTING SYSTEM USAGE AND ITS IMPACT ON SMES PERFORMANCE: IN THE CONTEXT OF INDUSTRY 4.0 OF INDIA (IITM Journal of Business Studies, 2025)
Studies have shown that companies are working  on creating digital technology to make better  decisions and stay ahead of their rivals. However,  these studies haven’t explored deeply how  companies use digital technology to enhance  their operations and impact value, particularly  for small and medium-sized enterprises (SMEs).  In this context, accounting information has  played a crucial role in the decision-making  process of businesses, and the broad use of  digital technology has allowed for more efficient  and effective handling of accounting data  related to these activities. An online accounting  system called the AI-Driven Accounting  System generates the data required for research  while enabling the reporting, recording, and  processing of enormous amounts of money.  The current study focuses on the influence of  the TOE, or technological, organizational, and  environmental characteristics framework, on  AI-Driven Accounting System usage (AASU),  which, in turn, affects AI-Driven Accounting  System performance (AASP), in light of the  significance of AI-Driven Accounting Systems  for improving the financial performance  of SMEs. In order to examine the variables  influencing SMEs’ adoption of AI-Driven  accounting systems, this study created an  integrated model. The data collection tool for  this study was a questionnaire created from a  review of the literature. After analyzing data  from 183 working professionals of SMEs in  Gujarat and Haryana, India, structural equation  modeling (SEM) was performed using IBM  SPSS AMOS, Ver-20. The results demonstrate  that compatibility of using technology,  organizational preparedness, management at  senior level, and government support—all these  variables had an influence on using AI-Driven  Accounting System (AASU) except in the  Relative Advantage of Technology context.  AASU also had a positive and substantial impact  on AI-Driven accounting system performance  (AASP). AASU has been demonstrated to be  an effective technology for the management  of large volumes of data, so it is expected that  its usage will increase in the near future.
Keywords: Government Support; AI-Driven Accounting System Usage (AASU); Technological Context; Organizational Preparedness; SMEs